Balancing the benefits and detriments among women targeted by the Norwegian Breast Cancer Screening Program. (December 2016) - Hofvind, Solveig; Román, Marta; Sebuødegård, Sofie; Falk, Ragnhild S
Objective: To compute a ratio between the estimated numbers of lives saved from breast cancer death and the number of women diagnosed with a breast cancer that never would have been diagnosed during the woman's lifetime had she not attended screening (epidemiologic over-diagnosis) in the Norwegian Breast Cancer Screening Program. Methods: The Norwegian Breast Cancer Screening Program invites women aged 50–69 to biennial mammographic screening. Results from published studies using individual level data from the programme for estimating breast cancer mortality and epidemiologic over-diagnosis comprised the basis for the ratio. The mortality reduction varied from 36.8% to 43% among screened women, while estimates on epidemiologic over-diagnosis ranged from 7% to 19.6%. We computed the average estimates for both values. The benefit–detriment ratio, number of lives saved, and number of women over-diagnosed were computed for different scenarios of reduction in breast cancer mortality and epidemiologic over-diagnosis. Results: For every 10, 000 biennially screened women, followed until age 79, we estimated that 53–61 (average 57) women were saved from breast cancer death, and 45–126 (average 82) were over-diagnosed. The benefit–detriment ratio using average estimates was 1:1.4, indicating that the programme saved about one life per 1–2 women with epidemiologic over-diagnosis. Conclusion: The benefit–detriment ratio estimates of the Norwegian Breast Cancer Screening Program, expressed as lives saved from breast cancer death and epidemiologic over-diagnosis, should be interpreted with care due to substantial uncertainties in the estimates, and the differences in the scale of values of the events compared.